Towards smear-free anemia diagnosis: evidence from a high-volume laboratory - Sanyal, Kaninika; Kotru, Mrinalini (International Journal of Research in Medical Sciences, 2025)
Background: Objectives of the study were to evaluate whether peripheral smear (PS) examination is essential in all cases of moderate anemia, or if automated hematology analyzer parameters—particularly RBC indices, red cell distribution width (RDW), and reticulocyte count—can provide reliable diagnostic information. Methods: This retrospective audit was conducted in the hematology laboratory of a tertiary care teaching hospital over six months. A total of 707 consecutive cases of moderate anemia (hemoglobin 8–10 g/dl) were included. Cases were classified by automated RBC indices into microcytic, macrocytic, normocytic normochromic (NCNC), or dimorphic categories. Peripheral smears were reviewed independently by two hematopathologists. RDW and reticulocyte count were analyzed for additional diagnostic utility. Concordance between analyzer-based and smear-based classifications was evaluated using contingency tables and Chi-square testing (χ²=504, df=24, p<0.001). One-way ANOVA with post-hoc Tukey analysis assessed differences in RDW values across anemia subtypes. Results: Microcytic anemia demonstrated the highest concordance between analyzer and smear findings (83.8%), followed by macrocytic (56%), dimorphic (40.8%), and NCNC anemia (17.5%). Hemolytic anemia showed no concordance. Elevated RDW values effectively flagged hidden mixed morphologies, while reticulocyte counts were useful in distinguishing regenerative states. Dimorphic anemia exhibited significantly higher RDW compared to both microcytic and macrocytic anemia (p<0.05). Conclusion: Selective smear review, guided by RBC indices, RDW, and reticulocyte counts, ensures diagnostic accuracy while reducing workload. Universal smear policies are impractical in high-volume laboratories, and targeted approaches provide an evidence-based balance between accuracy and efficiency.